An Assessment into Pre-service Biology Teachers' Approaches to the Theory of Evolution and Nature of Science - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2011)
This study explores how a group of pre-service biology teachers view the nature of evolutionary theory and how their views about nature of science affect their approaches to the theory of evolution. A total number of 75 pre-service teachers participated in the study. Participants' perceptions of nature of science and the theory of evolution were assessed by a questionnaire and a semi-structured, face-to-face interviews. The results revealed that the participants generally had negative attitudes toward the nature and status of the theory of evolution. Furthermore, a detailed analysis of participants' accounts with regard to the nature of science and the examination of the association of these accounts with their views about the theory of evolution implied a potential relationship.
Keywords: nature of science; the theory of evolution; pre-service biology teachers; STUDENTS PERCEPTIONS; TEACHING EVOLUTION; COLLEGE-STUDENTS; CONCEPTIONS; VIEWS; ACCEPTANCE; BELIEFS